Removable Partial Denture Treatment In A Patient With Angle Class III Malocclusion And Traumatic Anterior Deep Bite: A Case Report - Reyhan Ageng Brahmantya; Retno Sari (CV. AFDIFAL MAJU BERKAH, 2026)
Malocclusion is a deviation from normal occlusion that reflects an imbalance between the teeth, facial bones, and soft tissues; according to Edward H. Angle, it is classified into Classes I, II, and III. In Class III malocclusion, in addition to sagittal deviation, it may also be accompanied by a vertical abnormality in the form of a deep bite. A deep bite is a vertical malocclusion characterized by an increased incisal overbite, to the extent that the mandibular incisors may contact the palatal gingiva in severe cases. This condition can affect masticatory function, aesthetics, and occlusal stability. Tooth loss in patients with a deep bite can exacerbate occlusal disharmony, necessitating appropriate prosthodontic rehabilitation through the use of removable partial dentures (RPD). This case report discusses the fabrication of a removable partial denture for a patient with deep bite. A 24-year-old woman presented to Soelastri Dental Hospital complaining of loss of maxillary anterior teeth due to an accident two years prior. Clinical and radiographic examinations revealed the absence of teeth 11 and 21 and the presence of an interdental gap between teeth 23 and 24, accompanied by a deep bite classified as Applegate-Kennedy Class IV. The use of a removable partial denture (RPD) in patients with a deep bite requires comprehensive prosthodontic planning, particularly regarding occlusal relationships, retention, stability, and the distribution of masticatory forces. Properly designed acrylic resin RPD can yield good results in improving masticatory function, aesthetics, comfort, and the patient’s adaptation to wearing dentures. Acrylic resin removable partial dentures in patients with deep bite has shown good results, characterized by adequate retention and stability of the prosthesis, optimal patient adaptation, and improvements in masticatory function, aesthetics, and comfort through comprehensive prosthodontic planning.